Mechanisms of the anti-hypertensive effect of Hibiscus sabdariffa L. calyces - Ajay, M.; Chai, H.J.; Mustafa, A.M.; Gilani, A.H.; Mustafa, Mohd Rais (Elsevier, 2006)
Previous studies have demonstrated the anti-hypertensive effects of Hibiscus sabdariffa L. (HS) in both humans and experimental animals. To explore the mechanisms of the anti-hypertensive effect of the HS, we examined the effects of a crude methanolic extract of the calyces of HS (HSE) on vascular reactivity in isolated aortas from spontaneously hypertensive rats. HSE relaxed, concentration-dependently, KCl (high K+, 80 mM)-and phenylephrine (PE, 1 M)-pre-contracted aortic rings, with a greater potency against the 1-adrenergic receptor agonist. The relaxant effect of HSE was partly dependent on the presence of a functional endothelium as the action was signiﬁcantly reduced in endothelium-denuded aortic rings. Pretreatment with atropine (1 M), l-NAME (10 M) or methylene blue (10 M), but not indomethacin (10 M), signiﬁcantly blocked the relaxant effects of HSE. Endothelium-dependent and -independent relaxations induced by acetylcholine and sodium nitroprusside, respectively, were signiﬁcantly enhanced in aortic rings pretreated with HSE when compared to those observed in control aortic rings. The present results demonstrated that HSE has a vasodilator effect in the isolated aortic rings of hypertensive rats. These effects are probably mediated through the endothelium-derived nitric oxide-cGMP-relaxant pathway and inhibition of calcium (Ca 2+)-inﬂux into vascular smooth muscle cells. The present data further supports previous in vivo ﬁndings and the traditional use of HS as an anti-hypertensive agent.